Regulation of proteasomal assembly by intrinsic factors in bacteria and extrinsic factors in eukaryotes - Suppahia, Anjana (Kansas State University, 2019)
Proteasomes are large, multimeric proteases that are found in all eukaryotes, archaea and some bacteria. They function in a highly regulated manner to coordinate the recognition, unfolding and degradation of cellular proteins. At the center is the core particle (CP), a highly conserved dyad-symmetric structure composed of 28 subunits, that harbors the active sites in its cylindrically shaped structure. While the subunit complexity of CP in prokaryotes is low, with generally two unique subunits, alpha and beta, the eukaryotes possess a large number of paralogs and contain 14 unique subunits, seven different alpha and seven different beta subunits. The efficient and accurate assembly of the eukaryotic CP complex also depends on five different chaperones. In contrast, the prokaryotic CP assembles autonomously into active CPs. The work in this dissertation focuses on understanding the regulation of bacterial assembly pathways through intrinsic factors, using Rhodococcus erythropolis as a model. The bacterial beta subunits possess an N-terminal propeptide sequence that has previously been described to function as an intrinsic chaperone that promotes the formation of alpha-beta heterodimers early in the assembly. Our results, however, indicate additional functions for the propeptide in assembly. Our data indicate that a flexible region of propeptide regulates the dimerization of larger assembly intermediates called the half-proteasomes (HP). The dimerization of HPs results in the formation of an inactive form of CP which undergoes a conserved autocatalytic mechanism to cleave the propeptide sequences to form active CPs. Our data showed a role of the N-terminal region of propeptide in regulating this activation process of assembled CP. Based on the results of in vitro approaches, we propose a model where propeptide regulate the activation process through a cooperative mechanism involving the cleavage of propeptides. Eukaryotic 26S proteasomes consist of a CP capped on one or both ends by regulatory particle (RP). The assembly of CP and RP complexes requires ten unique assembly chaperones which are subsequently removed during the formation of RP-CP complexes. When studying the effects of the absence of the CP chaperone Ump1, that shares functionality with the bacterial propeptides described above, we observed the association of RP chaperones as well as Ecm29, a proteasome associated protein, on the proteasomes. Our data suggest a function of Ecm29, in preventing the release of chaperones from RP-CP complexes. Our results showed that the upregulation or overexpression of Ecm29 even in wildtype cells stabilizes RP chaperones on mature, functional 26S proteasomes. We also observed that the nucleotide state of specific ATPases found in the RP complex influences the stabilization of chaperones on 26S proteasomes. The ATPase mutants defective in ATP hydrolysis suggested that the hydrolysis of ATP is essential for the release of chaperones from RP-CP complexes. Our results imply a novel functional role of Ecm29 in recruiting or stabilizing RP chaperones on 26S thereby either assisting the RP base assembly or regulating the RP-CP interaction.
Keywords: Proteasomes